Essential involvement of the CX3CL1-CX3CR1 axis in bleomycin-induced pulmonary fibrosis via regulation of fibrocyte and M2 macrophage migration. Issue 1 (December 2017) - Ishida, Yuko; Kimura, Akihiko; Nosaka, Mizuho; Kuninaka, Yumi; Hemmi, Hiroaki; Sasaki, Izumi; Kaisho, Tsuneyasu; Mukaida, Naofumi; Kondo, Toshikazu
Abstract The potential role of macrophages in pulmonary fibrosis (PF) prompted us to evaluate the roles of CX3CR1, a chemokine receptor abundantly expressed in macrophages during bleomycin (BLM)-induced PF. Intratracheal BLM injection induced infiltration of leukocytes such as macrophages into the lungs, which eventually resulted in fibrosis. CX3CR1 expression was mainly detected in the majority of macrophages and in a small portion of α-smooth muscle actin-positive cells in the lungs, while CX3CL1 was expressed in macrophages. BLM-induced fibrotic changes in the lungs were reduced without any changes in the number of leukocytes inCx3cr1 −/− mice, as compared with those in the wild-type (WT) mice. However, intrapulmonary CX3CR1+ macrophages displayed pro-fibrotic M2 phenotypes; lack of CX3CR1 skewed their phenotypes toward M1 in BLM-challenged lungs. Moreover, fibrocytes expressed CX3CR1, and were increased in BLM-challenged WT lungs. The number of intrapulmonary fibrocytes was decreased inCx3cr1 −/− mice. Thus, locally-produced CX3CL1 can promote PF development primarily by attracting CX3CR1-expressing M2 macrophages and fibrocytes into the lungs.